P2.100 Clinical Efficacy of Sitafloxacin 100Mg Twice Daily For 7 Days For Patients with Non-Gonococcal Urethritis. (13th July 2013) - Takahashi, S; Hamasuna, R; Yasuda, M; Ito, S; Deguchi, T; Matsumoto, T
Abstract : To date, the standard treatment for the patients with chlamydial non-gonococcal urethritis (NGU) remains effective; however, conventional quinolone antibiotics have less activity against Mycoplasma genitalium-positive NGU. The purpose of this study was to establish the treatment efficacy of sitafloxacin (STFX), one of the new generation of quinolones, for patients with NGU. Male patients with NGU were included in this study. Chlamydia trachomatis was detected by TMA assay and M. genitalium and Ureaplasma urealyticum were detected by real-time PCR. The patients received STFX 100mg twice daily for 7 days orally. The primary outcome was microbiological eradication at 2 to 4 weeks after completion of treatment. A total of 208 patients were initially included in this study; however, 18 who were Neisseria gonorrhoeae-positive, 36 who failed to visit again, 34 who visited within 2 weeks after completion of treatment, 1 who had sexual intercourse with his female partner, and 1 whose data was lost were excluded from further analysis. In the 118 patients who could be analysed, the microbiological eradication rates were 95.7% (45/47) for C. trachomatis, 93.8% (15/16) for M. genitalium, and 100% (17/17) for U. urealyticum. The results of this study clearly show that STFX has strong activity against C. trachomatis, M. genitalium and U. urealyticum, which are common pathogens of NGU. The regimen with STFX for patients with NGU should be recommended as a standard one.